Um republicano histórico no Espírito Santo da Primeira República: a carreira de Bernardo Horta de Araújo (1887-1913) - Santos, Adilson Silva (2009)
Bernardo Horta de Araújo career as the Republic advertiser has its initial mark with the creation of the Espírito Santo first republican club, in Cachoeiro de Itapemirim, south of this province, on 23/05/1887, and its ending on 20/02/1913, when in Rio de Janeiro, he committed suicide. With the Republic proclamation, on 15/11/1889, Bernardo Horta acts as a protagonist in the implantation process of this new regime, having decisive participation on the most important political happenings of this period, sometime as a situation, sometime as an opposer, and the main aim is to verify how his political trajectory reflects the relationship between the municipal power and the state oligarchy. Besides, this work investigates the composition of the county government in Cachoeiro de Itapemirim and how it was constituted, as well as to relate the politicians who had important participation in the state oligarchy, i.e. Bernadino Monteiro, Pinheiro Jr., Jerônimo Monteiro, Marcondes Alves de Souza, highlighting Bernardo Horta de Araújo. The first chapter talks about the Republican advertise and the Espirito Santo republic installation and institutionalization first years, the Republican Party division, ending with the State Constitution approval and the election of Moniz Freire as the state governor. The second chapter is analyzing Cachoeiro de Itapmirim municipal politics and its relation to the state politics, emphasizing the municipal elections of this period. The third and last chapter focuses Bernado Horta political actuation as a Federal Deputy and his relationship to the municipal politics, ending with his suicidal. Among the found results is the composition of Cachoeiro de Itapemirim municipal governs over the period searched, the politicians, who had participation in the municipal, state and federal politics, careers, as well as the existence of a power geography which turned around the county basis, Muqui and Castelo.